Architecting the Future Enterprise - Nightingale, Deborah; Rhodes, Donna (Ascent Audio, 2018)
In this book, enterprise architecting experts Deborah Nightingale and Donna Rhodes offer a framework for enterprise transformation. Successful transformation, they believe, starts with a holistic approach, taking into consideration all facets of the enterprise and its environment rather than focusing solely on one factor-information technology, for example, or organizational structure. This is architecting the future enterprise: creating a blueprint for what the enterprise will look like after the transformation. Nightingale and Rhodes introduce the ARIES (Architecting Innovative Enterprise Strategy) framework, including a ten enterprise element model and an architecting process model, and show how to apply it, from start to finish. They explain how to create a holistic vision for the future enterprise and how to generate concepts and alternative architectures; they describe techniques for evaluating possible architectures, tools for implementation planning, and strategies for communicating with stakeholders.